Effect of Hyperbaric Oxygen on Proliferation and Gene Expression of Human Chondrocytes: An In Vitro Study. (October 2019) - Melcher, Carolin; Sievers, Birte; Höchsmann, Nadine; Düren, Frank; Jansson, Volkmar; Müller, Peter E.
Purpose: The present study investigated the effects of hyperbaric oxygen (HBO) on human chondrocyte proliferation and gene expression patterns. Methods: Chondrocyte cultures were transferred to a HBO chamber and exposed to 100% oxygen for 7 consecutive days. Within groups, pressure was varied between 1 and 2 atm and duration of HBO administration was varied among 60, 90, and 120 minutes. Cell counts were performed using the WST-1 assay at 1, 3, 5, and 7 days after initiation of HBO treatment to obtain data to plot a growth curve. Gene expression of apoptosis markers PARP and caspase 3, as well as cartilage specific proteins collagen II and COMP, were detected by reverse transcription polymerase chain reaction. Results: The experiments showed that in vitro administration of HBO inhibit chondrocyte growth. When applied compression was increased up to 2 atm, chondrocyte cell count was reduced by half at days 3 and 7 in association with an upregulation of the apoptosis markers PARP and caspase 3 as well as the cartilage specific proteins collagen II and COMP. No significant differences were monitored from varied duration of daily treatment. Conclusion: Chondrocyte growth was inhibited in vitro by treatment of HBO. This inhibitory effect was even increased by elevating the applied pressure, while molecular testing showed reduced chondrocyte growth. Higher levels of HBO inhibited cell growth even more, but up-regulation of apoptosis specific markers and cartilage specific proteins were seen during administration of high oxygen levels. Thus, it has to be evaluated that there is a critical level of hypo-/hyperoxia required to stimulate or at least maintain chondrocyte cell proliferation.